ANALISIS KREDIT MACET (PT. BANK SULUT, TBK DI MANADO) - Mewoh, Fransisca Claudya; J Sumampouw, Harry; F Tamengkel, Lucky (JURNAL ADMINISTRASI BISNIS, 2016)
This study is based on that: The extension of credit by the bank must pay attention to the principles of sound lending. To gain confidence, such as the explanation of Article 8 of Law No. 10 of 1998 on banking, namely: